Effects of Moodle Instructional Strategy on Achievement of Pre-Service Biology Teachers in Tertiary Institutions in South-West Nigeria - Olawale, Mutiat Y. (NIU Journal of Educational Research; Vol 11 No 2 (2025): NIU Journal of Educational Research, Vol. 11, No. 2, June 2025DO - 10.58709/niujed.v11i2.2239, 2025)
This study examined the impact of Modular Object-Oriented Dynamic Learning Environment (MOODLE) instruction on the achievement of pre-service teachers in vertebrate physiology in South West Nigeria. The study was guided by two research questions, and two null hypotheses were tested at a 0.05 level of significance. A quasi-experimental pre-test and post-test research design was employed for the study. The Vertebrate Physiology Achievement Test (VPAT) served as the data collection instrument, with its reliability established using Kuder Richardson 21 (Kr21), yielding a reliability coefficient of 0.74. Data analysis involved the use of mean, standard deviation, and Analysis of Covariance (ANCOVA) to test the hypotheses at a 0.05 significance level. Findings revealed that the application of Moodle significantly enhanced pre-service teachers' achievement in vertebrate physiology. Additionally, the results indicated no significant difference in the achievement of male and female pre-service Biology teachers exposed to vertebrate physiology instruction via Moodle. Based on these findings, it was recommended that biology lecturers incorporate Moodle in teaching pre-service teachers to promote higher achievement in vertebrate physiology. K eywords : Moodle, Achievement, Vertebrate Physiology, Pre-Service Teachers